Composite MCM-41/ZSM-5 as a cracking catalyst for the production of liquid fuel from used palm oil - Ooi, Yean-Sang; Zakaria, Ridzuan; Mohamed, Abdul Rahman; Bhatia, Subhash (Penerbit Universiti Sains Malaysia, 2004)
The gradual depletion of fossil fuel and drastically increase of the price of petrol have driven researchers looking into a new source of sustainable energy resources. Biofuel production from vegetable oils such as canola oil (Idem et al., 1996) and palm oil (Twaiq et al., 2003) are recently being studied over different types of cracking catalysts. With biofuel produced from the vegetable oil, the green house effect and air pollution can be minimized due to the recycling of carbon source from the air to the plant in closed cycle compare to the fossil fuels. Nevertheless, the high cost of the vegetable oil in comparison to the price of fossil fuel was one of the main reasons for not taking off the growth of biorefinery for production of fuels and chemicals from sustainable resources.